PENDAMPINGAN KEWIRAUSAHAAN SEBAGAI UPAYA MEWUJUDKAN LANSIA TANGGUH DI POSYANDU USILA MELUR KELURAHAN BANTAN - Hodriani; Berutu, Nurmala; Siregar, Zulkarnain; Rahmi, Anna; Listia, Wan Nova; Junaidi (Jurnal Abdi Insani, 2024)
The Bantan Subdistrict falls into the Ageing Population category, with 29% of its population being elderly. There are an estimated 1,444 pre-elderly individuals aged 45-49 and 4,438 elderly individuals aged 50 and above. Currently, many elderly individuals in Bantan become burdens to their children's families, requiring care and financial support, which ultimately affects the family's economy. Consequently, numerous elderly individuals remain unproductive, staying idle at home, leading to health issues among them. The aim of this program is to enhance the health and well-being of the elderly by fostering entrepreneurial spirit based on local food, thereby stimulating community economic growth. The implementation method consists of Preparation Phase, including systematic activity planning, brainstorming, Focus Group Discussions (FGDs), and Pre-Event. The Implementation Phase involves Pre-Incubation, Application, Incubation, and Post-Incubation Period. Evaluation includes Pre-test and Post-test. Results indicate that the entrepreneurship socialization and mentoring for the elderly in Bantan's IX Subdistrict proceeded smoothly and had a significant positive impact. Before the intervention, participants had an average knowledge score of 31.25. However, after participating in the socialization and mentoring activities, there was a significant increase in the average knowledge score, reaching 78.25, with an average score increase of 47.00, reflecting substantial improvement. It can be concluded that the program runs smoothly and well. The various efforts that have been made by the Unimed Team show their seriousness and commitment in empowering the elderly.